Seafarers' mental health during the COVID-19 pandemic: An examination of current supportive measures and their perceived effectiveness. (November 2022) - Tang, Lijun; Abila, Sanley; Kitada, Momoko; Malecosio, Serafin; Montes, Karima Krista
Abstract: As the current COVID-19 pandemic and the resulting crew change crisis exacerbates the mental health problem faced by seafarers, various maritime stakeholders have mobilised their resources and strengths to provide a variety of supportive measures to address the issue. This paper aims to find out what measures have been adopted in the industry and how widely they have been experienced/received by seafarers and evaluate their effectiveness. To achieve this aim, this research employed a mixed methods design involving qualitative interviews with 26 stakeholders and a quantitative questionnaire survey of 817 seafarers. The research identified a total number of 22 mental health support measures, all of which were perceived to have contributed positively to seafarers' mental health. However, not all of them were widely available to or utilised by seafarers. The findings also highlighted the importance of family, colleagues, shipping companies, and government agencies, as they are associated with the most effective support measures, namely communication with family, timely crew changes, being prioritised for vaccination, being vaccinated, and a positive and collegial atmosphere on-board. Based on the findings, recommendations are provided.